Autophagy‐related genes serve as heat shock protein 90 co‐chaperones in disease resistance against cassava bacterial blight. (21st June 2021) - Wei, Yunxie; Zeng, Hongqiu; Liu, Wen; Cheng, Xiao; Zhu, Binbin; Guo, Jingru; Shi, Haitao
SUMMARY: Heat shock protein 90 (HSP90) is involved in plant growth and various stress responses via regulating protein homeostasis. Autophagy keeps cellular homeostasis by recycling the components of cellular cytoplasmic constituents. Although they have similar effects on cellular protein homeostasis, the direct association between HSP90 and autophagy signaling remains unclear in plants, especially in tropical crops. In this study, the correlation between HSP90 and autophagy signaling was systematically analyzed by protein–protein interaction in cassava, one of the most important economy fruit in tropic. In addition, their effects on plant disease response and underlying mechanisms in cassava were investigated by functional genomics and genetic phenotype assay. The potential MeHSP90.9‐MeSGT1‐MeRAR1 chaperone complex interacts with MeATGs and subsequently triggers autophagy signaling, conferring improved disease resistance to cassava bacterial blight (CBB). On the contrary, HSP90 inhibitor and autophagy inhibitor decreased disease resistance against CBB in cassava, and autophagy may be involved in the potential MeHSP90.9‐MeSGT1‐MeRAR1 chaperone complex‐mediated multiple immune responses. This study highlights the precise modulation of autophagy signaling by potential MeHSP90.9‐MeSGT1‐MeRAR1 chaperone complex in autophagy‐mediated disease resistance to CBB. Significance Statement: This study reveals the correlation between a certain threshold of heat shock protein 90 (HSP90) activity and autophagy signaling as well as their effects on plant disease responses in cassava. We highlight the precise modulation of autophagy signaling by the potential MeHSP90.9‐MeSGT1‐MeRAR1 chaperone complex, which is essential for autophagy‐mediated disease resistance against CBB.